Kepemimpinan Transformasional untuk Memakmurkan Masjid Pada Masyarakat Urban - Maulana, Nasrul Arief (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2022)
The success of prospering mosques in urban communities cannot be separated from the leadership of the chairman of the takmir to mobilize mosque administrators and volunteers. The organizational transformation process can run more effectively through the use of a transformational leadership style. This leadership is widely used in the corporate environment, even though mosques, including in urban communities, need to carry out organizational transformation so that they can become the center of local community activities. This study aims to formulate transformational leadership initiated by Bernard M. Bass in prospering mosques in urban communities. This study includes a qualitative study with a theoretical adaptation design. The results of the study are transformational leadership carried out by takmir leaders to prosper mosques in urban communities, namely (1) communicating the thoughts of mosque functions to mosque administrators and volunteers in a persistent and consistent manner, (2) understanding the conditions and character of each administrator and mosque volunteers, then facilitating the development of the skills needed, (3) motivating administrators and mosque volunteers to contribute and build closeness in order to create a conducive environment for the prosperity of mosques, (4) creating a work environment that encourages the creativity of mosque administrators and volunteers through communication and consistency of leader behavior.